2019
DOI: 10.1002/lary.28044
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐infiltrating lymphocyte quantification stratifies early‐stage human papillomavirus oropharynx cancer prognosis

Abstract: Objectives/Hypothesis To evaluate if a simple method for assessing tumor‐infiltrating lymphocytes (TIL) in primary tumor specimens improves the prognostic value of the American Joint Committee on Cancer, 8th Edition (AJCC8) cancer staging system in human papillomavirus–positive oropharyngeal squamous cell carcinoma (HPV‐OPC). Study Design Retrospective study. Methods In this study, TIL density was quantified on hematoxylin and eosin (H&E)–stained specimens from patients presenting to Johns Hopkins Hospital bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 55 publications
2
23
0
1
Order By: Relevance
“…Thus, the results of this study need to be taken in the context of this careful selection for definitive surgery. In the future, the selection of patients for certain treatments may also possibly be supported by genetic or immunological tumor profile information 54,55 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the results of this study need to be taken in the context of this careful selection for definitive surgery. In the future, the selection of patients for certain treatments may also possibly be supported by genetic or immunological tumor profile information 54,55 …”
Section: Discussionmentioning
confidence: 99%
“…According to reports, the median OS time was 7.5 months, and some patients show resistance (16,17). Additionally, several studies have reported that patients with a greater number of tumor-infiltrating lymphocytes display increased survival in HPV-positive and -negative oropharyngeal disease (18)(19)(20)(21). Therefore, there is a need to elucidate the specific immune phenotypes of tumor-immune relationships and identify novel immunological targets for the treatment of HNSC.…”
Section: Introductionmentioning
confidence: 99%
“…As such, an important prognostic biomarker being investigated is the quantification of tumorinfiltrating lymphocytes (TILs). In fact, the prognostic value of TILs has been implicated in a variety of malignancies including colon cancer [4], bladder/urothelial cancer [5], oropharyngeal cancer [6], thyroid cancer [7], breast cancer [8], and melanoma [9,10].…”
Section: Introductionmentioning
confidence: 99%